Primary immunodeficiencies in highly consanguineous North African populations. - (:unkn) unknown (My University, 2011)
The study of inbred populations has contributed remarkably to the description of new autosomal recessive primary immunodeficiencies (PIDs). Here, we examine the pattern of PIDs in North African populations and assess the impact of highly prevalent consanguinity. This review reports on the current status of pediatricians' awareness of PIDs in Egypt, Morocco, and Tunisia, where awareness of PIDs is relatively recent. The phenotypic distribution of PIDs is reported and compared among the three countries and with other populations. Data analysis reveals a prevalence of autosomal recessive forms and a peculiar distribution of major PID categories, particularly more combined immunodeficiencies than antibody disorders. In these endogamous communities, molecular diagnosis is critical to developing a genetic-based preventive approach. The organization of diagnosis and care services in these resource-limited settings faces many obstacles. Autosomal recessive PIDs are overrepresented; thus, it is critical to continue investigation of these diseases in order to better understand the underlying mechanisms and to improve patient care.
Keywords: African Research